The US versus the North Korean nuclear threat : mitigating the nuclear security dilemma - Tan, Er-Win. (London : Routledge, 2014)
'Although the current world order is still dominated by the US, there is increasing international concern over the possibility of regional security dilemmas arising from smaller powers' attempts to develop Weapons of Mass Destruction. A study of US-North Korean interaction using the security dilemma as a conceptual frame of analysis is thus not only hugely topical, but also particularly relevant for the 21st century on theoretical as well as empirical grounds. Is there the prospect of a security dilemma contagion if North Korea acquire nuclear weapons capability leading to an Asia Pacific wide nuclear arms race? This book examines this contentious issue in-depth and explores the difficult choices policymakers face as a result of the uncertainty in international politics'--
'A study of US-North Korean interaction using the security dilemma as a conceptual frame of analysis is thus not only hugely topical, but also particularly relevant for the 21st century on theoretical as well as empirical grounds. Is there the prospect of a security dilemma contagion if North Korea acquire nuclear weapons capability leading to an Asia Pacific wide nuclear arms race? This book examines this contentious issue in-depth and explores the difficult choices policymakers face as a result of the uncertainty in international politics'--
Includes bibliographical references and index.
Keywords: Nuclear arms control -- Korea (North); Nuclear crisis control -- Korea (North); Security, International; United States -- Foreign relations -- Korea (North); Korea (North) -- Foreign relations -- United States